Quirinus and his Role in Original Capitoline Triad - Šmerda, Martin (Sapiens ubique civis, 2020)
This article is focused mainly on ancient Roman god Quirinus and his origin, character and role in the First Capitoline Triad of ancient roman religion. This article enumerates theories and views of Roman authors on the origin and character of Quirinus as one of the oldest members of ancient Roman pantheon. The available evidence from literary sources pertaining to Quirinus, his priests and festivals is also considered. Author of this article evaluates the similarities between Mars and Quirinus and their priests (Salii and flamines) and possible warlike competences of Quirinus – his connection to war.